EMPAT PILAR KEHIDUPAN BERBANGSA DAN BERNEGARA DALAM PARADIGMA PENDIDIKAN ISLAM - Usman Abu Bakar (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2015)
In today's world, Islamic education is facing a significant dilemma. On one hand, there is a need to modernize the concept and practice of Islamic education. On the other hand, it cannot afford to lag behind in the global competition, as it is an ongoing process. The current challenge lies in continuously improving the quality of Islamic education, especially in response to global developments. Failure to respond to global changes may lead to an ideological crisis that jeopardizes the identity of its citizens. Tauhid-oriented education is believed to be effective in addressing global phenomena and nurturing socially conscientious individuals. Moreover, as an education system, it is imperative for a nation to cultivate the character of its citizens while preserving the nation's values. The article proposes the four pillars as an alternative approach to revitalizing Indonesia, with a focus on human resource development, fostering good citizenship, and modernizing Islamic education.